2022
DOI: 10.1155/2022/9135172
|View full text |Cite
|
Sign up to set email alerts
|

SPR-Based Sensor for the Early Detection or Monitoring of Kidney Problems

Abstract: SPR-based technology has emerged as one of the most versatile optical tools for analyzing the binding mechanism of molecular interaction due to its inherent advantages in sensing applications, such as real-time, label-free, and high sensitivity characteristics. SPR is widely used in various fields, including healthcare, environmental management, and food-borne illness analysis. Meanwhile, kidney disease has grown to be one of the world’s most serious public health problems in recent decades, resulting in physi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 100 publications
(128 reference statements)
0
3
0
Order By: Relevance
“…In addition, the histological study showed no alteration of the liver structure. Renal dysfunction can be evaluated by simultaneous measurements of urea, creatinine and uric acid [18,26]. In this study, there were no changes in plasma levels of urea and creatinine of treated rats compared to controls rats.…”
Section: Discussionmentioning
confidence: 54%
“…In addition, the histological study showed no alteration of the liver structure. Renal dysfunction can be evaluated by simultaneous measurements of urea, creatinine and uric acid [18,26]. In this study, there were no changes in plasma levels of urea and creatinine of treated rats compared to controls rats.…”
Section: Discussionmentioning
confidence: 54%
“…The establishment of a bioimaging platform for detecting AKI and screening the therapeutic effects of drugs stands out as one of the most popular strategies for advancing clinical practice today. For such, a variety of bioimaging techniques including plasmonic and electrochemical detectors, the incorporation of nanoparticles, and a variety of biorecognition components (e.g., antibodies, , aptamers, molecular imprinting molecules are applied to improve the detector’s capacity for diagnosis …”
Section: Bioimaging Strategies For Akimentioning
confidence: 99%
“…These resonant plasma oscillations generate intense electromagnetic fields that extend outward from the nanoparticle surface into the surrounding medium, decaying evanescently away from the interface. Generally, the penetration depth of the evanescent field is on the order of tens to hundreds of nanometers, providing an intense localized electromagnetic field that can interact with and enhance the signature of target biomarker molecules within this distance [42].…”
Section: Definition and Explanation Of Lspr Phenomenon In Noble Metal...mentioning
confidence: 99%